2014
DOI: 10.1021/sc500548c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Copolymerization of Fully Biobased Benzoxazines from Renewable Resources

Abstract: A solventless method was adopted to synthesize two benzoxazine monomers from naturally occurring sources, i.e., eugenol (an extraction from clove), furfurylamine, stearylamine, and paraformaldehyde. The structure of the extracted eugenol and synthesized monomers were supported by FT-IR, 1 H NMR, 13 C NMR, and mass spectral analysis. The monomers were polymerized/copolymerized via ring-opening polymerization by heating as shown by FT-IR (disappearance of the peak due to oxazine ring at 920 cm −1 ) and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
129
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 29 publications
(60 reference statements)
3
129
0
Order By: Relevance
“…[15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36][37][38] ). [15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…[15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36][37][38] ). [15] Up to now,alarge quantity of biobased benzoxazines have already been prepared from the renewable cardanol, [16,17] diphenolic acid, [18,19] phloretic acid, [20] furfurylamine, [21,22] stearylamine, [23] coumarin, [24,25] umbelliferone, [26] and more recently the lignin derivatives (guaiacol, [27][28][29][30] vanillin, [31][32][33] and eugenol [34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…Among additives, ame retardants (FR) represent a signicant group whose use is crucial in many sectors where re safety is a major issue (building, transportation, electronics.). 20 Up to now, there have been only a limited number of papers reporting bio-based solutions for epoxy ame retardancy. 9 One promising way consists in preparing FR from renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…bio-based benzoxazines by Ishida, who found that monomers based on coumarin are photopolymerizable and that the surfaces of corresponding polymers have good hydrophobicity. 31 Cádiz synthesized a series of tough benzoxazine resins using castor oil, 32 and eugenol was used to synthesize a series of bio-based benzoxazines and composite materials by Thirukumaran et al 33 Furfurylamine and stearylamine are widely used by researcher to synthesize fully bio-based benzoxazines. It has been reported that furan ring structures can participate in benzoxazine crosslinking reactions and improve the crosslinking density of the system.…”
Section: Introductionmentioning
confidence: 99%